1997
DOI: 10.1128/jb.179.13.4446-4450.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the Streptomyces peucetius dnmZUV genes encoding three enzymes required for biosynthesis of the daunorubicin precursor thymidine diphospho-L-daunosamine

Abstract: Characterization of the dnmZ, dnmU, and dnmV genes from the daunorubicin-producer Streptomyces peucetius by DNA sequence analysis indicated that these genes encode a protein of unknown function plus a putative thymidine diphospho-4-keto-6-deoxyglucose-3(5)-epimerase and thymidine diphospho-4-ketodeoxyhexulose reductase, respectively. Inactivation of each of the three genes by gene disruption and replacement in the wild-type strain demonstrated that all of them are required for daunosamine biosynthesis.Daunorub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 29 publications
0
46
0
2
Order By: Relevance
“…Comparison of the deduced product of this gene with proteins in databases showed clear similarities with various dTDP-4-keto-6-deoxyglucose 3,5-epimerases involved in 6-deoxysugar biosynthesis in the streptomycin pathway by Streptomyces glaucescens (50% identity; PIR accession no. S44236), the StrM epimerase from S. griseus, which is also involved in streptomycin biosynthesis (50% identity) (40), the EryBVII protein from the erythromycin pathway from S. erythraea (42.4% identity) (16,53), and the DnmU protein from the daunorubicin pathway in S. peucetius (42.8% identity) (37). OleL also resembles different RfbC proteins involved in lipopolysaccharide biosynthesis in Mycobacterium tuberculosis (7) and Shigella flexneri (30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of the deduced product of this gene with proteins in databases showed clear similarities with various dTDP-4-keto-6-deoxyglucose 3,5-epimerases involved in 6-deoxysugar biosynthesis in the streptomycin pathway by Streptomyces glaucescens (50% identity; PIR accession no. S44236), the StrM epimerase from S. griseus, which is also involved in streptomycin biosynthesis (50% identity) (40), the EryBVII protein from the erythromycin pathway from S. erythraea (42.4% identity) (16,53), and the DnmU protein from the daunorubicin pathway in S. peucetius (42.8% identity) (37). OleL also resembles different RfbC proteins involved in lipopolysaccharide biosynthesis in Mycobacterium tuberculosis (7) and Shigella flexneri (30).…”
Section: Resultsmentioning
confidence: 99%
“…However, the biochemical pathways involved in 6-deoxyhexose biosynthesis have not been characterized in most cases. Several authors have reported the cloning of different genes involved in the biosynthesis of 6-deoxyhexoses in antibiotic and antitumor pathways: streptomycin (40), erythromycin (10,16,46,53), tylosin (15,19,31), daunosamine (36,37), lincomycin (38), mithramycin (28), methymycin-pikromycin (62), and granaticin (4,22). Macrolide antibiotics contain mono-or disaccharides attached to the macrolactone rings which are important for activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, however, cosubstrate availability can be an issue. For example, glycosyltransferases associated with polyketide pathways often utilize specialized TDP-deoxysugars, themselves the products of multistep biosynthetic pathways (26,66,80). As with PKS genes, the clustering of the genes responsible for TDP-sugar biosynthesis facilitates their expression in heterologous hosts (64).…”
Section: Post-pks Polyketide Modificationmentioning
confidence: 99%
“…The high-copy-number Streptomyces shuttle vector pWHM3 was from Vara et al (1989), and the low-copynumber shuttle vector pWHM601 was from Guilfoile & Hutchinson (1991). pWHM219 was from Otten et al (1997), pWHM533 was from Otten et al (1995), pWHM1104 was from Tang et al (1996), and pWHM289 and pWHM298 were from Lomovskaya et al (1999). pMT3000 and the promoter probe vector pMT3003.1 (Paget et al, 1994) were provided by C. P. Smith (University of Manchester, UK).…”
Section: Our Studies Of the Molecular Biology Of Daunorubicin (Dnr) Amentioning
confidence: 99%